Characterization at high spatial and angular resolutions of deformed nanostructures by on-axis HR-TKD. (August 2020) - Ernould, Clément; Beausir, Benoît; Fundenberger, Jean-Jacques; Taupin, Vincent; Bouzy, Emmanuel
Abstract: Global Digital Image Correlation (DIC) is applied on the electron diffraction patterns acquired by the "on-axis" Transmission Kikuchi Diffraction (TKD) technique. High-angular resolution (HR-TKD) mappings of the grain internal disorientations and the associated geometrically necessary dislocation densities are then derived at a nanoscale resolution. Tailored for the fine characterization of nanomaterials in the scanning electron microscope (SEM), the method is illustrated on a nanostructured high-purity aluminium processed by severe plastic deformation (SPD) and its performances are discussed in the light of imaging by transmission electron microscopy (TEM) and by SEM using a forescatter electron detector (FSD). Graphical abstract: Image, graphical abstract